2009
DOI: 10.1002/ajmg.a.33015
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of TFAP2A gene involvement in branchio‐oculo‐facial syndrome (BOFS) and report of temporal bone anomalies

Abstract: Branchio-oculo-facial syndrome (BOFS) is an autosomal-dominant condition characterized by three main features, respectively: branchial defects, ocular anomalies, and craniofacial defects including cleft lip and/or palate (CL/P). We report on one family with three affected, and two sporadic cases that have been found to carry missense mutations in the newly reported BOFS gene: TFAP2A. This report confirms the involvement of this transcription factor in this developmental syndrome with clinical variability. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…NC-derived tumors particularly include melanoma, neuroblastoma, neurofibroma, medullary thyroid cancers, and pheochromocytoma. For instance, mutations in TFAP2A lead to branchiooculofacial syndrome, where anomalies of the external and middle ear frequently cause conductive hearing loss [90,91] (see also OMIM entry 113620). These craniofacial defects particularly include the Saethre-Chotzen syndrome, a failure of neural tube closure related to heterozygous TWIST1 mutation leading to craniosynostosis and facial dysmorphism [88] (see also OMIM entry 101400).…”
Section: The Role Of Sex In Neuronal Development and Neural Stem Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…NC-derived tumors particularly include melanoma, neuroblastoma, neurofibroma, medullary thyroid cancers, and pheochromocytoma. For instance, mutations in TFAP2A lead to branchiooculofacial syndrome, where anomalies of the external and middle ear frequently cause conductive hearing loss [90,91] (see also OMIM entry 113620). These craniofacial defects particularly include the Saethre-Chotzen syndrome, a failure of neural tube closure related to heterozygous TWIST1 mutation leading to craniosynostosis and facial dysmorphism [88] (see also OMIM entry 101400).…”
Section: The Role Of Sex In Neuronal Development and Neural Stem Cellmentioning
confidence: 99%
“…While inner ear neurocristopathies arise from melanocyte defects, craniofacial neurocristopathies of the outer and middle ear can be caused by NC developmental defects of bone and cartilage [89]. For instance, mutations in TFAP2A lead to branchiooculofacial syndrome, where anomalies of the external and middle ear frequently cause conductive hearing loss [90,91] (see also OMIM entry 113620). The Treacher Collins-Franceschetti syndrome is also associated with NC maldevelopment, where a TCOF1 mutation leads to NC apoptosis and causes among others deformity of the ears, conductive hearing loss, and cleft palate [92] (see also OMIM entry 154500).…”
Section: Adult Neural Crest-derived Stem Cells and Sex-specific Diffementioning
confidence: 99%
“…Although studies in knockout mice (reviewed in reference 9) and of phenotypically related inherited human traits (25,32) have shown that these factors have important functions during embryogenesis, they are minimally expressed in most adult tissues. However, expression of the TFAP2A and TFAP2C proteins has been demonstrated in a variety of solid tumors, including breast cancer and melanoma (reviewed in reference 24).…”
mentioning
confidence: 99%
“…However, there is evidence for clinical heterogeneity [Stoetzel et al, 2009;Tekin et al, 2009]. The phenotype varies from severe to very mild between family members carrying the same genetic defect [Milunsky et al, 2008;Stoetzel et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, not known if TFAP2A is mutated in the atypical BOFS patients [Stoetzel et al, 2009].…”
mentioning
confidence: 99%